Sustained production of superoxide radicals by manganese oxides under ambient dark conditions. (15th May 2021) - Zhang, Suhuan; Lv, Jitao; Han, Ruixia; Wang, Zhe; Christie, Peter; Zhang, Shuzhen
Highlights: O2 - can be sustainably formed by MnO2 in the dark. Surface Mn(III) plays a key role in the formation of O2 − . Sustained production mechanism of O2 - by MnO2 were revealed. O2 - contributed to the transformation of various halophenols by MnO2 . Abstract: Manganese (Mn) oxides are ubiquitous in the environment and have strong reactivity to induce the transformation of various contaminants. However, whether reactive oxygen species contribute to their surface reactivity remains unclear. Here, sustainable production of superoxide radicals (O2 − ) by various MnO2 polymorphs in the dark was quantified and the mechanisms involved were explored. The results confirm that O2 − was produced through one-electron transfer from surface Mn(III) to adsorbed O2 . In contrast, no H2 O2 was detected due to its decomposition by Mn oxides to form O2 − and Mn(III), leading to the sustained production of O2 − on Mn oxide surfaces. In addition, the production of O2 − was found to make a clear contribution (4 – 28%) to the transformation of a series of halophenols by MnO2, suggesting that the O2 − -mediated surface reaction is an important supplement to the direct electron-transfer mechanism in the reactivity of Mn oxides. These findings advance our understanding of the surface reactivity of Mn oxides and also reveal an important but hitherto unrecognized abiotic source of O2 − in the natural environment. Graphical abstract: Image, graphical abstract